The Effect of Selenium on Pathogenicity and Mortality of COVID-19: Focusing on the Biological Role of Selenium (Journal of Pharmaceutical Negative Results, 2022)
In the last two years, coronavirus infections increased the mortality rate among the elderly and especially patients who suffer from chronic diseases. Despite vaccination, many people are still dying from COVID-19. Among these, the role of minerals in increasing the function of the immune system and combating coronavirus infection has been proven. Selenium (Se) is a crucial valuable element for human health with a determinative in decreasing the amount of ROS produced in response to different viral infections within the body. The role of selenoprotein enzymes in struggling oxidative caused by ROS overproduction is very important. The overall function of cytotoxic cells increases by the presence of selenium. Recent clinical trials carried out on patients with COVID-19 have demonstrated that the deficiency of selenium is obvious in patients who suffer from acute respiratory infections. Due to the role of selenium in viral inflammation, it is expected that this substance will prevent the cytokine storm and ultimately mortality of infected people by reducing the production of inflammatory cytokines. The present study investigates the role of selenium and selenoproteins and their possible mechanisms in the pathogenesis of viral infections. Further comprehension on the the role of the pathogenesis of viral infections and their mortality could be achieved through identifying potential selenoproteins in the COVID 19 genome by means of computational tools. The following core competencies are addressed in this article: The effect of selenium on pathogenicity and mortality of COVID-19.